PENGARUH BUDAYA ORGANISASI DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN BAGIAN ANTARAN PT POS INDONESIA SPP SEMARANG - Gradinawan Imantaka Ramadhan; Endang Sulistiyani; Luqman Khakim (Politeknik Negeri Semarang, 2019)
This study aimed to determine the influence of organizational culture and work facility on employees performance at the delivery department of PT Pos Indonesia SPP Semarang. The method that used for data collection in this study were observation, questionnaires, and literature review. The total sample determination were calculated using Slovin formula. It obtained 60 sample of respondents wich were chosen by using incidental sampling. Hypotheses were constructed as four hypotheses and tested using multiple linear regression analysis. The data analysis methods that has been used in this study were Instrumental test, Classic Assumption Test, Multiple linear regression analysis, and Hypothesis Test. The results of this study find out that organizational culture and work facility are partialy had a positive significant influence on employees performance. Simultaniously, organizational culture and work facility are partialy had a positive significant influence on employees performance. Work facility had the biggest influence in increasing employees performance.